DIVERSITAS TERIPANG (HOLOTHUROIDEA) DI ZONA INTERTIDAL PANTAI MARINA WAKATOBI - Kusrini, Kusrini (Lembaga Penelitian dan Pengabdian Masyarakat FKIP UMB, 2023)
The presence of sea cucumbers does not attract much attention, but their presence greatly influences the richness of marine biota and the diversity of biota species in the waters. Live in groups or spread out and are widely found in waters with a substrate of sand, coral sand, or sand mixed with mud. The substrate for Marina beach waters is sand, sand dominated by sea grass, sand with a little Acropora type coral, and sand mixed with mud and stones. Such conditions allow the growth and development of sea cucumbers. This study aims to determine the diversity of sea cucumbers (Holothuroidea) in the intertidal zone of Marina Wakatobi beach. This type of research is an experiment with cruise methods covering an area of ​​+ 500m2 in the intertidal zone of Marina Wakatobi beach. The types of sea cucumbers found were Synapta maculata, Holothuria scabra, Holothuria atra, Actinopyga echinites, Bohadschia marmorata, Holothurian hilla. Holothuria scabra is a type of sea cucumber that has a high distribution.